The Usage of Paracetamol and Ibuprofen in Children with Persistent Ductus Arteriosus - . Yulistiani (Journal of Global Pharma Technology, 2019)
Backgrounds: Persistent Ductus Arteriosus (PDA) is the structure of the ductus arteriosus that failed to close after the birth of the baby. One of the therapies which are used to overcome the closure of PDA is pharmacological therapy using prostaglandin inhibitors. Aim: to determine usage profiles, including dosage, frequency, route, and duration of paracetamol administration and ibuprofen for DAP. In addition, it also assesses the actual outcomes and side effects of using paracetamol and ibuprofen in children with PDAs. Method: this research was a quantitative research with a retrospective method. The sampling method used random sampling. The total sample was 32 children who were hospitalized with diagnosis of PDA with or without complications. Data was collected by conducting an assessment of the patient's medical record to the documentation sheet.  Results: Based on research in 32 patients, 78% of patients received paracetamol therapy, 16% of patients received ibuprofen, and 6% of patients received replacement therapy for paracetamol to ibuprofen. From 25 patients who received paracetamol therapy, 12 patients (48%) gave the outcome of PDA closure and eliminated patient tachypnea and cyanosis. The average dose of paracetamol used for PDA is 7.5-15 mg / kg every 6 hours for 3-7 days by oral route (9%) and intravenously (63%).While the average dose of ibuprofen for PDAs is 10 mg / kg / day for the first day and 5 mg / kg / day for the second and third days by oral route (100%). Conclusion: the use of paracetamol and ibuprofen for PDAs was in accordance with existing literature relating to the dose, route, frequency, and duration of administration for PDAs. However, there were some patients with special conditions that require adjustment of the second dose of the drug. The use of paracetamol and ibuprofen for PDAs did not cause actual side effects. The use of paracetamol for PDAs needs to be further investigated regarding the effectiveness and drug related problems and the need to consider the use of ibuprofen for PDAs related to potential side effects that can be caused.Keywords: Patent ductus arteriosus, Paracetamol, Ibuprofen, Pediatrics.